The Role of Self-Regulated Learning on Learners' Learning Independence: A Review of the Literature - Hadiyati, Intan Pratiwi; Matsuri, Matsuri; Santosa, Eka Budhi (Universitas Sebelas Maret, 2026)
Learning independence is an essential competency that supports students in managing their learning actively and responsibly. This study aims to examine the role of self-regulated learning in enhancing students’ learning independence through a Systematic Literature Review (SLR) using the PRISMA framework. Data were collected from articles published between 2016 and 2026 in Google Scholar, Springer, Frontiers, and MDPI, then analyzed descriptively and visualized using VOSviewer. The results show that self-regulated learning contributes significantly to students’ learning independence, particularly in goal setting, time management, self-monitoring, and self-evaluation. Bibliometric analysis also indicates a strong relationship between self-regulated learning, learning motivation, and learning independence. Therefore, self-regulated learning is an important factor that should be integrated into the learning process to improve students’ learning independence.